Effect of Fiber Orientation on Mechanical Properties of Kenaf-Reinforced Polymer Composite - Yong, C.K.; Ching, Yern Chee; Chuah, Cheng Hock; Liou, N.S. (North Carolina State University, 2015)
The increase of environmental awareness has led to interest in the use of materials with eco-friendly attributes. In this study, a sandwich composite was developed from polyester and kenaf fiber with various orientation arrangements. Polyester/kenaf sandwich composite was fabricated through the combination of a hand lay-up process and cold compression. The tensile, flexural, and Izod impact tests of the sandwich composites were evaluated by using a universal tensile tester and an impact tester. The thermal stability of polyester/kenaf sandwich composite and plywood were investigated by using a thermogravimetric analyser. Results showed that the polyester/kenaf sandwich composite with kenaf fiber in anisotropy orientation achieved the highest mechanical properties. The kenaf fiber in anisotropic orientation could absorb the impact energy and allow the sandwich composite to withstand greater impact forces compared to composite with fiber in perpendicular or isotropic orientations. The polyester/kenaf sandwich composite also showed higher thermal stability compared to a conventional plywood sheet. Thus, the fabrication of polyester/kenaf sandwich composite with kenaf fiber in an anisotropic orientation design has great potential to replace plywood sheets for beam construction applications.